Development of Numerical Method Course Modules Based on Creative Thinking Ability - Lukmanul Akhsani; Anton Jaelani; Agung Purwo Wicaksono (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
The Numerical Method is one of the introductory courses that are useful for students to understand mathematics better. However, the reality on the ground is that students do not understand the material in this course and only use problem-solving methods without understanding its meaning. This research is development research. This research aims to describe the results of the numerical method course module's development, efficiency and effectiveness based on creative thinking. This study uses a modified Thiagarajan development model in three stages: the define, design, and developing stages. This research was conducted with the subjects of fourth-semester students who took the Numerical Method course in the mathematics education study program at the Muhammadiyah University of Purwokerto. This research produces a product from a numerical method course module. Based on the analysis results at the define stage, students still do not interpret the material in the numerical method course, so their creative thinking skills tend to be poorly trained. At the design stage, the module is prepared by training students with creative thinking skills. Finally, at the development stage, the module is validated and tested in the numerical method course. The validation results state that the module is valid and can be used with minor revisions. Furthermore, after being tested, the students' responses were found to be in good criteria, meaning that the module was constructive for students. Then, the results of the creative thinking ability test stated that the results of the creative thinking ability test of students who used the development result module experienced mastery learning. Based on these results, it is concluded that the numerical method course module based on creative thinking skills is valid, practical and effective. Keywords: development, numerical method, creative thinking.